Gymnema inodorum (Lour.) Decne. Extract Alleviates Oxidative Stress and Inflammatory Mediators Produced by RAW264.7 Macrophages. (4th February 2021) - Dunkhunthod, Benjawan; Talabnin, Chutima; Murphy, Mark; Thumanu, Kanjana; Sittisart, Patcharawan; Eumkeb, Griangsak
Abstract : Gymnema inodorum (Lour.) Decne. ( G. inodorum ) is widely used in Northern Thai cuisine as local vegetables and commercial herb tea products. In the present study, G. inodorum extract (GIE) was evaluated for its antioxidant and anti-inflammatory effects in LPS plus IFN- γ -induced RAW264.7 cells. Major compounds in GIE were evaluated using GC-MS and found 16 volatile compounds presenting in the extract. GIE exhibited antioxidant activity by scavenging the intracellular reactive oxygen species (ROS) production and increasing superoxide dismutase 2 (SOD2) mRNA expression in LPS plus IFN- γ -induced RAW264.7 cells. GIE showed anti-inflammatory activity through suppressing nitric oxide (NO), proinflammatory cytokine production interleukin 6 (IL-6) and also downregulation of the expression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and IL-6 mRNA levels in LPS plus IFN- γ -induced RAW264.7 cells. Mechanism studies showed that GIE suppressed the NF- κ B p65 nuclear translocation and slightly decreased the phosphorylation of NF- κ B p65 (p-NF- κ B p65) protein. Our studies applied the synchrotron radiation-based FTIR microspectroscopy (SR-FTIR), supported by multivariate analysis, to identify the FTIR spectral changes based on macromolecule alterations occurring in RAW264.7 cells. SR-FTIR results demonstrated that the presence of LPS plus IFN- γ in RAW264.7 cells associated with the increase of amide I/amide II ratio (contributing to the alteration of secondary protein structure) and lipid content, whereas glycogen and other carbohydrate content were decreased. These findings lead us to believe that GIE may prevent oxidative damage by scavenging intracellular ROS production and activating the antioxidant gene, SOD2, expression. Therefore, it is possible that the antioxidant properties of GIE could modulate the inflammation process by regulating the ROS levels, which lead to the suppression of proinflammatory cytokines and genes. Therefore, GIE could be developed into a novel antioxidant and anti-inflammatory agent to treat and prevent diseases related to oxidative stress and inflammation.